2021
DOI: 10.1017/s1368980021000355
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of households at risk for food insecurity in the United States during the COVID-19 pandemic

Abstract: Objective: To examine associations between sociodemographic and mental health characteristics with household risk for food insecurity during the COVID-19 outbreak. Design: Cross-sectional online survey analyzed using univariable tests and a multivariable logistic regression model. Setting: The United States during the week of March 30, 2020. Participants: Convenience sample of 1,965 American adults using Amazon’s Mechanical Turk (MTurk) platform. Parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 19 publications
5
66
1
2
Order By: Relevance
“…Research on food insecurity during COVID-19 at the national and local levels and among high-risk populations, such as lowincome, low education, and Black, Indigenous, and people of color (BIPOC), are emerging throughout the United States. Studies have commonly reported or projected increased rates of food insecurity during COVID-19 (4)(5)(6)(7)(43)(44)(45)(46)(47). National studies examining food insecurity, challenges, and worry have reported increased rates of food insecurity among low-income households (43,47), households with low education (6,43), BIPOC households (6,43,44,47), households with children (6,44,47), those experiencing employment disruption (6,43,44), and SNAP participants (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on food insecurity during COVID-19 at the national and local levels and among high-risk populations, such as lowincome, low education, and Black, Indigenous, and people of color (BIPOC), are emerging throughout the United States. Studies have commonly reported or projected increased rates of food insecurity during COVID-19 (4)(5)(6)(7)(43)(44)(45)(46)(47). National studies examining food insecurity, challenges, and worry have reported increased rates of food insecurity among low-income households (43,47), households with low education (6,43), BIPOC households (6,43,44,47), households with children (6,44,47), those experiencing employment disruption (6,43,44), and SNAP participants (6).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have commonly reported or projected increased rates of food insecurity during COVID-19 (4)(5)(6)(7)(43)(44)(45)(46)(47). National studies examining food insecurity, challenges, and worry have reported increased rates of food insecurity among low-income households (43,47), households with low education (6,43), BIPOC households (6,43,44,47), households with children (6,44,47), those experiencing employment disruption (6,43,44), and SNAP participants (6). A nationally representative study on low-income adults found that they were less able to comply with recommendations to stock up on 2 weeks of groceries and more likely to need extra money for food and bills (6).…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, food insecurity in the U.S. has been on the rise along with unemployment rates, with women, veterans, and Black, Hispanic, and Native Americans seeing the greatest increases in food insecurity [ 24 , 25 ]. Record numbers of people are seeking food assistance at food banks, and Feeding America estimates that the largest food bank network in the country will see a USD 1.4 billion shortfall [ 26 ].…”
Section: The Role Crises Play In Women’s Food Insecuritymentioning
confidence: 99%
“…(1,2) In particular, Black, Hispanic, and Asian adults are at the highest risk of being food insecure during the pandemic. (3,4) During the peak of the pandemic, Black food-insecure households were more likely to report they could not afford to purchase more food during the pandemic and Hispanic food-insecure households were more likely to report they are afraid or do not want to go out to purchase food during the pandemic. (5) The traditional food system, which includes grocery stores and convenience stores, has failed individuals because food hoarding and disruptions to the food supply left grocery store shelves bare, (6) while increased food prices due to price volatility prevented individuals from purchasing the food that they needed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%